Dissecting the molecular trajectory of fibroblast reprogramming to chemically induced mammary epithelial cells - Qin, Liangshan; Zhang, Dandan; Liu, Siyi; Liu, Quanhui; Liu, Mingxing; Huang, Ben (Frontiers in Cell and Developmental Biology, 2023)
The plastic of cell identity allows cellular reprogramming that manipulate the lineage of cells to generate the target cell types, brings new avenues for disease modeling and autologous tailored cell therapy. Previously, we had already successfully established a technical platform of inducing fibroblast reprogramming to chemically induced mammary epithelial cells (CiMECs) by small molecule compounds. However, exactly how the molecular mechanism driving the lineage conversion remains unknown. Here we employ the RNA-sequencing technology to investigate the transcriptome event during the reprogramming process, and reveal the molecular mechanisms for the fate acquisition of mammary lineage. We found the multi-step reprogramming process first overcome multiple barriers, including the inhibition of mesenchymal characteristics, pro-inflammatory and cell death signal, then enter an intermediate plastic state. Subsequently rapidly activated the hormone and mammary development genes, and finally acquire mammary program together with upregulation of the milk protein synthesis signal. Moreover, the gene network analyses reveal the potential relationship between TGF-β signaling pathway to mammary lineage activation, and the changes in the expression of these genes may play important roles in coordinate the reprogramming process. Together, these findings provide critical insights into the molecular route and mechanism that triggered by small molecule compounds inducing fibroblast reprogramming into the fate of mammary epithelial cells, and laid a foundation for the subsequent research on the development and differentiation of mammary epithelial cells and lactation.